A Byzantine Book on Dream Interpretation The Oneirocriticon of Achmet and Its Arabic Sources - Mavroudi, Maria V. (The Medieval Mediterranean, 2002)
This monograph compares the most important Byzantine work on dream interpretation with the 2nd-century A.D. Greek work of Artemidoros and five medieval Arabic dreambooks and demonstrates that it was based on Islamic Arabic sources adapted for Christian readers of Greek